2021
DOI: 10.1016/j.cmi.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

B- and T-cell immune responses elicited by the Comirnaty® COVID-19 vaccine in nursing-home residents

Abstract: Objectives: The immunogenicity of the Comirnaty® vaccine against coronavirus disease 2019 (COVID-19) has not been adequately studied in elderly people with comorbidities. We assessed antibody and T-cell responses targeted to the S protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) following full vaccination in nursing-home residents. Methods: Sixty nursing-home residents (44 female, age 53e100 years), of whom ten had previously been diagnosed with COVID-19, and 18 healthy controls (15 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…In conclusion, our data indicated that both antibody and peripheral blood CD4 + T-cell levels measured after Comirnaty® vaccination in elderly nursing home residents wane over time in line with previous findings 2 , 3 , 4 , 5 , 6 , 7 , 8 , declining significantly by 7M after vaccination, particularly in SARS-CoV-2 naïve individuals.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, our data indicated that both antibody and peripheral blood CD4 + T-cell levels measured after Comirnaty® vaccination in elderly nursing home residents wane over time in line with previous findings 2 , 3 , 4 , 5 , 6 , 7 , 8 , declining significantly by 7M after vaccination, particularly in SARS-CoV-2 naïve individuals.…”
supporting
confidence: 91%
“…Participants testing negative for SARS-CoV-2 antibodies by all the above assays (n=6) with available specimens (n=5) were examined for presence of SARS-CoV-2-S-reactive IFNγ‐producing T cells by whole-blood flow cytometry for intracellular cytokine staining (ICS), as previously described [ 2 , 3 ]. Four residents had detectable S-targeted CD8 + T cells (median, 0.47%; range, 0.16–3.94%), whereas none had CD4 + T cells.…”
mentioning
confidence: 99%
“…To do so, the ProVaVac program established a consortium that includes representatives of hospitals, universities and research centers working under the scientific direction of David Navarro to generate knowledge, promote the coordination and integration of research projects dedicated to post-vaccination follow-up, facilitate the establishment of synergies between different entities and research groups, and offering them the data support of the Public Health System of the Valencian Community. One example of the generation of research data for public service information on the vaccination strategy was the evaluation of the immunogenicity and long-term immunity of SARS-CoV-2 mRNA vaccines among the general population and nursing home residents ( Albert et al, 2022 ; Torres et al, 2021 ). The knowledge generated was then disseminated to the public and used to support health decision making and to implement strategies for high-risk patients, including administration of a third dose of Comirnaty in nursing home residents ( Gimenez et al, 2022 ) and the overall population of the Valencian Community.…”
Section: Regional National and European Network To Monitor Sars-cov-2...mentioning
confidence: 99%
“…In spite of this reassuring rate, very limited data were available about the vaccines' effectiveness on the geriatric population, as this population was not included in the BNT162b2 vaccine clinical trials [ 17 ]. Studies conducted later found that the vaccines' immunogenicity in the elderly population was lower than the general population, yet a certain level of protection was acquired [ 18 , 19 , 20 , 21 ]. Starting December 2020, the Senior Shield task force began vaccinating the residents and caregivers of LTCFs in Israel.…”
Section: Introductionmentioning
confidence: 99%